Factors influencing the utilization of guidance and counseling services among health training students at Mildmay Uganda School of Nursing and Midwifery. A cross-sectional study. - Nakabbo, Wariyyah; Nansereko, Hasifa; Nalubega, Jane Frank; Akankwasa, Edith (Student's Journal of Health Research Africa, 2025)
Background: In Uganda, 41% of health training students do not access structured counseling services during their study period. The purpose of the study was to assess the factors influencing the utilization of Guidance and Counseling Services among health training students at Mildmay, Uganda. Methods. A descriptive cross-sectional study design was used, employing quantitative methods of data collection, conducted in Mildmay Uganda School of Nursing and Midwifery. In 6 days, 90 students were selected using simple Stratified random sampling. A structured questionnaire was used to collect data, and it involved closed-ended questions. The data collected was analyzed manually, and after the findings were entered into a Microsoft Excel 2013, which was then presented in the form of tables, pie-charts, and graphs. Results. The majority (61%) were females, and 89% were single. 56% felt uncomfortable seeking them, 51% lacked peer support, and 56% were hindered by school work. Institutionally, 73% noted a shortage of counselors, 67% said the school did not actively promote counseling, 42% indicated inflexible counseling schedules, 46% acknowledged supportive leadership, and 100% stated that counseling was weakly integrated into academic programs. Conclusion. Despite high awareness of guidance and counseling services, their utilization among health training students was limited due to personal discomfort, lack of peer support, institutional constraints, and inadequate promotion and accessibility. Recommendation. The institution should strengthen the promotion, accessibility, and confidentiality of guidance and counseling services to enhance their utilization by students.